Response of Indian mustard (Brassica juncea L.) hybrids to different spacings on aridisols: RESPONSE OF INDIAN MUSTARD HYBRIDS TO DIFFERENT SPACINGS ON ARIDISOLS - BIKRAM SINGH; VIRENDER MALIK; AMARJEET; ABHA TIKKO; P K YADAV; JAGDEV SINGH (Journal of Oilseeds Research, 2016)
The field experiments on the performance of four hybrids/varieties viz., three newly released hybrids DMH 1, PAC 432 and NRCHB 506 and one best check variety of Indian mustard (Brassica juncea L.) with five crop geometries (30 cm x 10 cm, 30 cm x 15 cm, 45 cm x 10 cm, 45 cm x 15 cm and 60 cm x 10 cm) were conducted on Typic Ustochrept soil at Bawal, Haryana during rabi season for two consecutive years (2009-10 and 2010-11) under irrigated conditions. The experiment was laid out in split plot design with fourreplications. The pooled results of the study revealed that planting of Indian mustard hybrids viz., DMH 1, PAC 432 and NRCHB 506 at wider crop geometry of 45 cmx 15 cmrecorded highest seed yield of 2578, 2308 and 2023 kg/ha; and fetched maximumprofits (` 36714, ` 30784 and ` 24584) and benefit: cost ratio (2.80, 2.51 and 2.21), respectively than with other spacings. However, check variety Kranti proved superior with respect to seed yield (1807 kg/ha), net returns (` 19820/ha) and benefit: cost ratio (1.98) at a spacing of 30 cm x 15 cm. Among all hybrids tested, hybrid DMH1 was found significantly superior to others in respect of plant height (218 cm), primary branches/plant (8.79), siliquae/plant (408) and seeds/siliqua (16.18) except 1,000-seed weight (3.41 g). This hybrid also recorded 12.7, 29.7 and 50.9; 5.9, 24.0 and 36.7; 12.9, 29.4 and 55.7; and 23.0, 60.6 and 121.8 per cent higher seed yield, production efficiency, oil production and net returns over PAC 432, NRCHB 506 and Kranti, respectively.